ANALISIS MINAT INVESTOR SUKUK GENERASI Z TERHADAP SUKUK RITEL - Safitri, Ferdiana Yuliantika; Kornitasari, Yenny (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The global financial market in 2020 was weakened by the Covid-19 pandemic. Nevertheless, the interest on retail sukuk in Indonesia during the 2020-2021 period has increased, and Generation Z was the minor investor group of it. The objectives of this research are to identify and analyze the partial effects of financial literacy, knowledge about investment risk, yield rate, and religiosity on the interest of generation Z in Java to invest in retail sukuk and to identify factors with the most dominant effect of all. Using purposive sampling, 400 people regarded as Generation Z in Java were selected as the respondents. The data of this quantitative descriptive study were acquired from Likert-scaled questionnaires and analyzed using multiple linear regression. This research finds that financial literacy, knowledge about investment risk, yield rate, and religiosity partially have positive and significant effects on the interest of Generation Z in Java to invest in retail sukuk. Further, religiosity was found to be the most dominant factor affecting the interest of the said people to invest in retail sukuk.